IMPLEMENTASI MULTIPLATFORM MEDIA SOSIAL DALAM PEMASARAN KAMPUNG WISATA BAROKAH - Amalina, Husna Nur (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This study aims to analyze the use of social media multiplatforms in marketing Barokah Tourism Village located in Dukuh Pakel, Gerdu Village, Karangpandan District, Karanganyar Regency. Barokah Tourism Village has great potential to become a leading tourist destination. This research uses qualitative methods and collects data through observation, as well as content analysis of various social media platforms such as Instagram, Facebook, and YouTube. The results show that the use of social media multiplatforms can expand marketing reach, with each platform having its own role and advantages in attracting different audiences. Instagram is effective for attracting a visual audience, Facebook provides more in-depth information, while YouTube is used to present more detailed video content. In addition, a content strategy that focuses on visualizing the activities, activities and local culture that are offered attractively in the tourism village has proven to be effective in attracting audience attention. This study also found that consistency in managing content and interaction with audiences is essential to increase engagement and brand awareness. Based on these findings, it is recommended that the manager of Barokah Tourism Village continue to optimize the use of social media multiplatforms by paying attention to the characteristics of each platform and increasing active interaction with audiences to increase tourist visits.